Avaliação da viabilidade de intervenção adaptada do treinamento de habilidades em regulação emocional da terapia comportamental dialética para usuários de crack - Schneider, Jaluza Aimèe (2021)
Although crack use is a serious health problem at a national level, there is a scarcity of studies that seek to evaluate interventions with real potential for effectiveness, through feasibility studies, considering the subpopulations among users and the existing contextual specificities. Thus, this doctoral thesis had the general aim of contributing to the treatment of crack users, highlighting the relevance of emotional regulation skills for this population. The Introduction to this thesis briefly describes personal motivation and the theoretical-epistemological basis for the construction of the four studies that make up the theoretical and empirical sections. The theoretical section begins with study 1, entitled “History of violence and emotional regulation as risk factors for substance use disorders among women”. It is a book chapter that discusses emotional dysregulation among female crack users’ victims of some form of violence during their lifetime. The second theoretical study was a systematic review about clinical studies of interventions focusing on emotional regulation for substance use disorder, entitled “Emotional regulation interventions for substance users: a systematic review”. The empirical section begins with study 3, “Translation, cultural adaptation and validity evidence of the negative mood regulation scale for the Brazilian context”, which aimed to adapt a scale for assessing individual expectations of regulating negative emotions. The results indicated adequate psychometric evidence of validity and reliability for the Brazilian population. Finally, study 4, “Evaluation of the feasibility of an intervention adapted from the skills training in emotional regulation of dialectical behavioral therapy for crack users”, analyzed the feasibility of the intervention adapted for crack users through the criteria of demand, intervention adaptation, implementation, acceptability by the target sample and preliminary effectiveness data. The results indicated that the intervention contributed to the improvement in clinical indicators and proved to be viable for application in clinics for the treatment of these patients. Preliminary data on effectiveness suggest that the intervention may contribute to the treatment of patients and future studies with more robust designs may evaluate its effectiveness and efficacy.